Synthesis of potassium niobate (KNbO3) nano-powder by a modified solid-state reaction - Chaiyo, Nopsiri; Ruangphanit, Anucha; Muanghlua, Rangson; Niemcharoen, Surasak; Boonchom, Banjong; Vittayakorn, Naratip (My University, 2011)
Crystalline lead-free piezoelectric potassium niobate (KNbO3) powders have been synthesized through a modified solid-state reaction method. The thermal behavior of the K2C2O4-H 2O and Nb2O5 raw material mixture was investigated by thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The X-ray diffraction technique (XRD) was used to investigate the phase formation and purity. The morphology of the powder obtained was characterized using a scanning electron microscope (SEM). The XRD pattern showed that the monophasic perovskite phase of KNbO3 could be synthesized successfully at a temperature as low as 550 °C for 240 min, with an average crystallite size of 36 ± 8 nm. The SEM images suggested that the average particle size of the powder obtained was 278 ± 75 nm. © Springer Science+Business Media, LLC 2010.